2021
DOI: 10.34108/eujhs.783635
|View full text |Cite
|
Sign up to set email alerts
|

Kadinlarin Gebeli̇k Dönemi̇ndeki̇ Ağiz Di̇ş Sağliği Durumlari

Abstract: Gebelik dö neminde kadının ağ ız diş sağ lığ ı hem ğebe kadının, hem de döğ acak çöcuğ un ğelecek ağ ız diş sağ lığ ında belirleyici ölmasından dölayı çök ö nemlidir. Bu çalışmada kadınların ğebelik dö nemindeki ağ ız, diş sağlığ ı durumlarını belirlemek amacıyla yapılmıştır. Tanımlayıcı ve kesitsel tipte yapılan araştırmanın ö rneklemini Kırıkkale Ü niversitesi Hastanesi'ne başvuran döğ um aşamasındaki 212 kadın öluşturmuştur. Veriler literature dayalı ölarak hazırlanan anket förmu kullanılarak töplanmış, IBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In a study conducted in India, 62.5% of pregnant women reported that dental treatments must be performed before pregnancy and they avoided dental treatments during pregnancy (15). Studies conducted in different regions of Turkey report that the rates of going to the dentist during pregnancy are 12.4% and 28.3% (15,16). Although the rate of going to the dentist during pregnancy and the positive approach to dental treatment in this study is close to the results of some other studies in the literature, this rate seems to be insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in India, 62.5% of pregnant women reported that dental treatments must be performed before pregnancy and they avoided dental treatments during pregnancy (15). Studies conducted in different regions of Turkey report that the rates of going to the dentist during pregnancy are 12.4% and 28.3% (15,16). Although the rate of going to the dentist during pregnancy and the positive approach to dental treatment in this study is close to the results of some other studies in the literature, this rate seems to be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Kısa et al reported that the rate of women with regular tooth brushing was higher among the women in the age group of 20-29 (10). On the other hand, some studies do not take into account the age factor (16,23). Further studies evaluating sociodemographic characteristics and oral hygiene habits are needed.…”
Section: Discussionmentioning
confidence: 99%